Fullerene and omega-3 and omega-6 fatty acids on fish brain antioxidant status - Acosta, Daiane da Silva; Kneip, Flavia Conde; De Almeida, Eduardo Alves [UNESP]; Ventura-Lima, Juliane; Monserrat, Jose Maria; Geracitano, Laura Alicia (Springer, 2012)
The carbon nanomaterial fullerene (C-60) can act as anti or pro-oxidant. The aim of this study was to evaluate, in cell suspensions of carp brains (Cyprinus carpio, Cyprinidae), the effect of C-60 after a pre-treatment with polyunsaturated fatty acid (PUFAs) such as omega-3 (docosahexaenoic acid, DHA) and omega-6 (linoleic acid, LA). Assays consisted of a pre-treatment with PUFA (48 h) and then exposure to C-60 (2 h). Cell viability and total anti-oxidant capacity did not differ (p > 0.05). A reduction (p < 0.05) was observed in reactive oxygen species (ROS) and thiobarbituric acid reactive substances (TBARS) concentration in fish brain cells pre-exposed with PUFA groups and then exposed or not with C-60. An antioxidant effect of C-60 was evident since in control group (cells not pre-exposed to PUFA), a significant (p < 0.05) reduction of intracellular ROS concentration was observed, although this reduction was not enough to reduce the TBARS levels. Cysteine levels presented a reduction (p < 0.05) in all groups exposed to C-60. For glutathione (GSH), an increase (p < 0.05) was registered in cells exposed to C-60 without PUFAs pre-treatment and in the C-60 group pre-treated with DHA. Overall C-60 appears to play an antioxidant role that is modulated by PUFA, taking into account its effects on intracellular ROS concentration and MDA levels. Results also suggest that C-60 influences GSH synthesis, as showed for the augmented levels of this antioxidant and also for the lowering of the intracellular cysteine concentration.
Keywords: Fullerene; Polyunsaturated acids; Nanoparticles; Fish brain; Cysteine; Glutathione